Effects of recent prior dengue infection on risk and severity of subsequent SARS-CoV-2 infection: a retrospective cohort study - Tang, Nicole (2024)
Background and Aims. Elucidating whether prior dengue potentially confers cross-protection against COVID-19 is of public health importance in tropical countries at risk of overlapping dengue and COVID-19 epidemics. However, studies to date have yielded conflicting results. We aimed to assess effects of recent prior dengue infection on risk and severity of subsequent SARSCoV-2 infection among adult Singaporeans. Methods. A retrospective cohort study including all adult Singaporeans aged ≥18 years was conducted from 1 July 2021 through 31 October 2022, when a dengue outbreak driven by the DENV3 serotype preceded subsequent waves of SARS-CoV-2 Delta/Omicron transmission in Singapore. SARS-CoV-2 and dengue infection status were classified using national registries. Cox regression models adjusted for demographics, COVID-19 vaccination status, comorbidity, and socioeconomic-status were used to assess risks and severity (hospitalization, severe illness) of SARS-CoV-2 infection occurring after previous recorded dengue infection. Results. A total of 3 366 399 individuals were included, contributing 1 399 696 530 person-days of observation. A total of 13 434 dengue infections and 1 253 520 subsequent SARS-CoV-2 infections were recorded; with an average of 94.7 days (standard deviation = 83.8) between dengue infection and SARS-CoV-2 infection. Preceding dengue infection was associated with a modest increase in risk of subsequent SARS-CoV-2 infection (adjusted hazards ratio [aHR] = 1.13; 95% confidence interval [CI], 1.08–1.17), and significantly elevated risk of subsequent COVID-19 hospitalization (aHR = 3.25; 95% CI, 2.78–3.82) and severe COVID-19 (aHR = 3.39; 95% CI, 2.29–5.03). Conclusions. Increased risk of SARS-CoV-2 infection and adverse COVID-19 outcomes were observed following preceding dengue infection in a national population-based cohort of adult Singaporeans. This observation is of significance in tropical countries with overlapping dengue and COVID-19 outbreaks.